Prevalence of hypertension and related risk factors among children and adolescents at three separate visits: A large school-based study in China - Hu, Jia; Ding, Ziyao; Han, Di; Hai, Bo; Lv, Huiling; Yin, Jieyun; Shen, Hui; Gu, Aihua; Yang, Haibing (Frontiers in Pediatrics, 2022)
Objective We aimed to demonstrate characteristics of hypertension at three separate visits and its risk factors among children and adolescents based on a large school-based study in China. Materials and methods Based on a large-scale ongoing monitoring program conducted in Suzhou, China, 59,679 children and adolescents aged 7–17 years from 60 public schools were enrolled during 2020 to 2021. Height, weight, and blood pressure (BP) were measured. Additional BP would be measured for hypertensive students at least 2 weeks later. Confirmed hypertension was defined as simultaneously BP meeting above or equal to 95th percentile for age, sex, and height at three separate visits. Odds ratio (ORs), and 95% CIs were calculated by logistic regression to identify risk factors for hypertension. Results Prevalence of hypertension at three separate visits were 20.4, 6.3, and 3.1%, respectively. Prevalence of confirmed isolated systolic hypertension, isolated diastolic hypertension, and systolic and diastolic hypertension were 1.9, 0.3, and 0.9%, respectively. Hypertension prevalence for stages 1 and 2 were 2.6 and 0.6%. Different hypertension prevalence were found among various age and gender groups. Boys [OR, 1.137 (95% CI, 1.033–1.251)], high age [OR, 3.326 (95% CI, 2.950–3.751)], urban residents [OR, 1.579 (95% CI, 1.417–1.760)], high-socioeconomic status [OR, 1.156 (95% CI, 1.039–1.286)] and body mass index category including overweight [1.883 (95% CI, 1.665–2.129)], obesity [4.049 (95% CI, 3.625–4.523)], and thinness [OR, 0.457 (95% CI, 0.306–0.683)] were associated with confirmed hypertension. Conclusion A single BP measurement would overestimate hypertension prevalence, about 3% Chinese children were hypertensive, early, and effective intervention around risk factors for hypertension should be taken.